Trends in Tensions between Modelled Direction and Context in Education - Bruzgelevičienė, Ramutė (Pedagogika, 2018)
The article continues the analysis of the problem of tensions between the modelled direction and the context in education in Lithuania in the stage of its development in the second decade of the 21st century. The selected aspect – the opportunity for the transformational purpose of education declared in documents on education while social groups assess education unfavourably. The research question – why are there tensions between the declared transformational purpose of education and the context of development of education. The research is based on the qualitative methodology of documentary analysis: purposefully selected document sources of discourse on educational matters are analysed. Data analysis and interpretation and discussion of approaches by comparing them with theoretical perceptions and insights of researchers lead to conclude the following: All approach coalitions analysed in the discourse recognise transformational impact of education as a system on an individual and society, but treat the content of the impact completely differently. The representatives of business and politics coalitions rely in the discourse on the perceptions of education as socialisation and development of society as economic growth, therefore they would consider education good, if individuals were formed in accordance with the requirements of the business coalition, with no opportunities to choose the learning area, provision of knowledge of exact sciences, digital literacy and entrepreneurship required for economic growth rates, training the capacity to sell skills, instilling values and behavioural models for taking care of oneself, so that young people would as soon as possible be able to become the quality “human capital” creating added value, while the education system and policy would serve business and industrial development. This discourse coalition uses pervading economic criteria in assessing the intellectual resources and processes of education, and educational outcomes, and would use these criteria for modelling further direction of teaching individuals and developing education. Individual participants of discourse who by their occupation belong to the business coalition are guided by the perception of the development of society as long-term sustainable progress, i.e. they assess not only economic growth, but also the distribution of goods resulting from sustainable progress and the stability of progress. Although individual approaches do not represent a strong position in assessing education, their concepts serve the basis for raising the problem of equality of income and opportunities in society, which has a significant impact on educational outcomes: income inequality causes inequality of opportunities due to which some part of the youth is socially marginalised or is forced to emigrate. The discourse coalition of philosophers, sociologists, and psychologists relies on the perception of education as empowerment of an individual and as personal liberation, development of society as increasing choice opportunities and the process of revealing the capacity to form the world. Approaches of this coalition focus on the humanist relationship with the growing individual as the perspective of the nation, on a human being nurtured on the humanist level as a civic, thinking, creative and democratic individual, on the cognition of the world as an intrinsic value and as the way to search for intelligence, on knowledge which serves values, and also on many other values which essentially represent the provisions of educational policies adhered to in Lithuania in the second decade of the 21st century. Tensions between the provisions modelled in education and the understanding of the role of education in society, assessment of the condition of education, and further direction in which education should develop during the period researched by groups implementing education policy and different groups of society occur due to conflicting theoretical concepts, on which individual groups of society rely.